Stress hyperglycemia after pancreatobiliary surgeries - Joseph, Nishi Mary; Mammen, Sam Christy (International Surgery Journal, 2020)
Background: Diabetes mellitus is a common problem and stress hyperglycemia occurring in patients undergoing surgery without history of diabetes mellitus has been shown to have a poorer clinical outcome. Effective glycemic control in the perioperative period results in marked improvement in clinical outcome. Methods: This prospective study was conducted among 100 cases of the pancreatobiliary postoperative patients admitted in General Surgery Department, Government Medical College Kottayam during November 2015 to November 2016. The post-operative blood sugar values, age, sex, BMI, family history of diabetes mellitus, anemia, hypoproteinemia, intraoperative blood loss, intraoperative blood transfusion, duration of surgery, and type of surgery were studied with respect to occurrence of stress hyperglycemia. Results: The total incidence was 35%. The incidence in pancreatic surgery (87.5%), other biliary surgeries (77.8%), open cholecystectomy (31.2%) and laparoscopic cholecystectomy (18%). Significant association was found in malnourished and obese persons, anemia, hypoalbuminemia, duration of surgery more than 3 hours, intraoperative blood loss of more than 500 ml and intraoperative blood transfusion and pancreatic surgery. Independent predictors of stress hyperglycemia were found to anemia, hypoproteinemia, duration of surgery more than 3 hours and underweight and obese individuals. Conclusions: Stress hyperglycemia incidence in pancreatobiliary postoperative patients was found to be 35%. Independent predictors of stress hyperglycemia were anemia, hypoproteinemia, duration of surgery more than 3 hours and BMI <18.5 and >30. Hence correction of anemia, improving the nutritional status preoperatively and minimising the duration of surgery will improve the clinical outcome.